Effectiveness of self-management support program for overweight employees: a quasi-experimental study - Leawsoong, Supaporn; Pongsaengpan, Paiboon; Ouppawongsapat, Dhammawat; Piboon, Kanchana (International Journal of Public Health Science (IJPHS), 2025)
This quasi-experimental research examined the effects of self-management support program on knowledge, exercise and eating behaviors, body mass index (BMI), and waist circumference among overweight employees in an industry in Samutprakarn Province, Thailand. Seventy overweight employees aged 20-59 years were equally randomly allocated into either the treatment or control group. Thirty-five overweight employees were in each group. In the 16 weeks, the treatment group was intervened through a selfmanagement support program, while the control group received standard care. Research tools consisted of two parts: a self-management support program and questionnaires. The data were analyzed by using descriptive statistics, paired t-tests, and independent t-tests. The results after 16 weeks of the self-management program showed that its average scores of knowledges, exercise, and eating behavior were higher than the baseline and control group (p<.05) while scores of waist circumferences and BMI were lower than the baseline (p<.05). The findings of this study indicated that the self-management support program had outcomes that not only could improve knowledge, exercise and eating behavior, but also reduce BMI and waist circumference. It is suggested that the self-management support program should be applied in the organization to promote knowledge and modify the health behaviors of overweight employees in other industries.